Isolated Giant Primary Splenic Hydatid Cyst in a 10-Year-Old Boy: A Case Report - Ghabisha S; Ahmed F; Al-wageeh S; Al-shami E; Al-naggar K; Chowdhury U; Haider N; Al-yousofy F (Dove Medical Press, 2021)
Saif Ghabisha,1 Faisal Ahmed,2 Saleh Al-wageeh,1 Ebrahim Al-shami,2 Khalil Al-naggar,2 Umayir Chowdhury,3 Najm Haider,2 Fayed Al-yousofy4 1Department of General Surgery, Ibb University of Medical Science, Ibb, Yemen; 2Urology Research Center, Department of Urology, Al-Thora General Hospital, Ibb University of Medical Science, Ibb, Yemen; 3Student Research Committee, Shiraz University of Medical Sciences, Shiraz, Iran; 4Department of Pathology, Faculty of Medicine, Taiz University of Medical Science, Taiz, YemenCorrespondence: Faisal AhmedAl-Thora General Hospital, Alodine Street, Ibb, YemenEmail fmaaa2006@yahoo.comAbstract: Hydatid cyst (HD) disease is a parasitic infection produced by cysts containing the larval stage of Echinococcus granulosus. It occurs worldwide, but its prevalence is higher in the rural communities of some developing countries like Yemen, where sheep and cattle raising constitute a crucial component of the agricultural industry. This zoonotic disease spreads due to close contact humans with sheep and dogs. The most involved organs with HC are the liver and lungs. However, other organs may also foster it, such as the spleen, with an incidence rate of between 0.5% and 6%. To the best of our knowledge, primary involvement of the spleen by HC is very rare, and a few cases with isolated spleen HC in children were reported. In this study, a ten-year-old boy with a huge primary splenic HC is reported with chief chief complaint of pain and non-tender bulging in his abdomen’s left upper quadrant. A 20× 16× 18 cm splenic cystic mass was detected by ultrasonography (US) and confirmed by abdominal computed tomography (CT) scan without macroscopic involvement in other organs. Total splenectomy was carried out for hem. Pathological examinations revealed cystic hydatidosis. We describe this case of an isolated huge spleen HC, which was successfully treated with total splenectomy, focusing on the management and outcome of this disease.Keywords: case report, echinococcosis, hydatid cyst, primary, splenectomy